Maurice Samuel : life and letters of a secular Jewish contrarian - Levenson, Alan T. (Tuscaloosa : The University of Alabama Press, 2022)
"This short intellectual biography reassesses one of the premier Jewish humanists of the mid-twentieth century, the Rumanian-born, English-educated, American belletrist Maurice Samuel. Although he spoke in a staccato Midlands accent, Samuel left Manchester, England in 1913, joined the American Army, served in military intelligence in World War I, and became a United States citizen. Samuel resettled his family in Palestine in 1929, then returned to the US, and spent his most creative years in New York City. A diaspora intellectual, or "rootless cosmopolitan," as Alan Levenson describes him, Samuel made an indelible mark on many features of contemporary Jewish thought and culture"--
Intro -- Contents -- List of Figures -- Acknowledgments -- Introduction -- 1. The Making and Unmaking of a British Jewish Gentleman -- 2. The Fifty-Year Career of a Zionist Publicist -- 3. Moish Samuel: Forgotten Yiddishist -- 4. Polemics and Apologetics -- 5. The Fiction of Jewish Essentialism Exposed: Samuel and the Hebrew Bible -- Epilogue -- Notes -- Bibliography -- Index.
eBooks on EBSCOhost
Keywords: Samuel, Maurice, -- 1895-1972.; Samuel, Maurice, -- 1895-1972; Jews, Romanian -- New York (State) -- New York -- Biography; Yiddish literature -- History and criticism; Jewish authors -- New York (State) -- New York -- Biography; Zionists -- New York (State) -- New York -- Biography; Judaism -- 20th century; Jewish learning and scholarship; New York (N.Y.) -- Biography; Littérature yiddish -- Histoire et critique; Écrivains juifs -- New York (État) -- New York -- Biographies; Judaïsme -- Histoire -- 20e siècle.; Juifs -- Savoir et érudition.; Juifs roumains -- New York (État) -- New York -- Biographies; Jewish; HISTORY; Judaism; RELIGION; Zionists; Yiddish literature; Judaism; Jews, Romanian; Jewish learning and scholarship; Jewish authors; New York (State) -- New York; 1900-1999; Criticism, interpretation, etc; Biographies